2021
DOI: 10.5009/gnl20134
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Immunogenicity of Anti-Tumor Necrosis Factor Agents in Pediatric Patients with Inflammatory Bowel Disease

Abstract: Background/Aims: Anti-drug antibodies (ADAs) can develop during treatment with anti-tumor necrosis factor (TNF) agents. We aimed to investigate the factors associated with immunogenicity of anti-TNF agents in pediatric patients with inflammatory bowel disease (IBD) and observe the clinical course of ADA-positive patients. Methods: Pediatric IBD patients receiving maintenance treatment with anti-TNF agents who had been tested for ADAs against infliximab (IFX) or adalimumab (ADL) were included in this crosssecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 51 publications
1
0
0
Order By: Relevance
“…Kim et al measured these transient ADAs in 30% of pediatric patients with IBD in which initial ADAs were found. Although both groups found ADAs during treatment, they did not show worsening of the treatment due to the transient nature of these antibodies, a phenomenon also shown by Steenholdt et al [27][28][29]. Ungar et al conducted a prospective observational study and showed that of the patients developing persistent ADAs against IFX, 90% do so within the first year after treatment initiation, while transient ADAs were detected during the entirety of the IFX therapy, having less implication for the loss of response to IFX or adverse events [30].…”
Section: Discussionsupporting
confidence: 68%
“…Kim et al measured these transient ADAs in 30% of pediatric patients with IBD in which initial ADAs were found. Although both groups found ADAs during treatment, they did not show worsening of the treatment due to the transient nature of these antibodies, a phenomenon also shown by Steenholdt et al [27][28][29]. Ungar et al conducted a prospective observational study and showed that of the patients developing persistent ADAs against IFX, 90% do so within the first year after treatment initiation, while transient ADAs were detected during the entirety of the IFX therapy, having less implication for the loss of response to IFX or adverse events [30].…”
Section: Discussionsupporting
confidence: 68%